Fruit intake and abdominal aortic calcification in elderly women: A prospective cohort study - Bondonno, N.; Lewis, J.; Prince, R.; Lim, W.; Wong, G.; Schousboe, J.; Woodman, R.; Kiel, D.; Bondonno, C.; Ward, Natalie; Croft, K.; Hodgson, J. (MDPI Publishing, 2016)
© 2016 by the authors; licensee MDPI, Basel, Switzerland. Cardiovascular disease (CVD) is the leading cause of death worldwide. There is a consistent inverse relationship between fruit intake with CVD events and mortality in cross-sectional and prospective observational studies, but the relationship of fruit intake with measurements of atherosclerosis in humans is less clear. Nutritional effects on abdominal aortic calcification (AAC), a marker for subclinical intimal and medial atherosclerotic vascular disease, have not been studied previously. The aim of this study was to examine the cross-sectional relationship of total and individual fruit (apple, pear, orange and other citrus, and banana) intake with AAC, scored between 0 and 24. The current study assessed baseline data for a cohort of 1052 women over 70 years of age who completed both a food frequency questionnaire assessing fruit intake, and underwent AAC measurement using dual energy X-ray absorptiometry. AAC scores were significantly negatively correlated with total fruit and apple intakes (p < 0.05), but not with pear, orange or banana intakes (p > 0.25). In multivariable-adjusted logistic regression, each standard deviation (SD; 50 g/day) increase in apple intake was associated with a 24% lower odds of having severe AAC (AAC score >5) (odd ratio OR): 0.76 (0.62, 0.93), p = 0.009). Total and other individual fruit intake were not associated with increased odds of having severe AAC. Apple but not total or other fruit intake is independently negatively associated with AAC in older women.